Actin depolymerization-induced changes in proteome of Arabidopsis roots - Takáč, Tomáš; Bekešová, Slávka; Šamaj, Jozef (Journal of proteomics, 2017)
UNLABELLED: Actin cytoskeleton is a vital cellular structure primarily known for controlling cell integrity, division and expansion. Here we present a proteomic dissection of Arabidopsis roots treated by actin depolymerizing agent latrunculin B. Pharmacological disintegration of the actin cytoskeleton by latrunculin B caused downregulation of several proteins involved in the actin organization and dynamics. Moreover, this approach helped to identify new protein candidates involved in gene transcription, due to the altered abundance of proteins involved in mRNA nuclear export. Finally, latrunculin B negatively affected the abundance of abscisic acid (ABA) responsive proteins. SIGNIFICANCE: This article substantially contributes to the current knowledge about the importance of actin organization and dynamics in proteome remodelling. We employed gel based and gel free proteomic analyses and identified several new protein candidates and protein networks linking actin dynamics to the gene transcription and to the ABA response in Arabidopsis.
Keywords: Bridged Bicyclo Compounds, Heterocyclic; proteom; Thiazolidines; proteiny huseníčku; bicyklické sloučeniny heterocyklické; Latrunculin B; Actin Cytoskeleton; Proteomics; aktiny; ABA responsive proteins; Arabidopsis Proteins; Arabidopsis root; proteomika; polymerizace; Polymerization; Arabidopsis; Abscisic Acid; kořeny rostlin; thiazolidiny; mRNA export; Actins; Actin cytoskeleton; Proteome; kyselina abscisová; Plant Roots; mikrofilamenta